Nonconvex spectral optimization algorithms for reduced‐order H∞ LPV‐LFT controllers - Shi, Ye; Tuan, Hoang D.; Apkarian, Pierre (International journal of robust and nonlinear control, 2017)
Summary A novel sequential semi‐definite programming method is developed for optimization subject to rank constraints on matrix‐valued nonlinear functions of matrix decision variables, which arise in reduced‐order linear parameter varying‐linear fractional transformational control synthesis. The global convergence of the method is easily proven without any step size control. An intensive simulation shows the clear advantage of the proposed method over the state‐of‐the‐art nonlinear matrix inequality solvers. Copyright © 2017 John Wiley & Sons, Ltd.